Meningkatkan Kompetensi Guru dalam Menyusun Administrasi Penilaian Melalui Penerapan Supervisi Akademik di SD Inpres XXXVII Kota Uneng - Konsolina Konsolina (Universitas Maritim AMNI Semarang, 2022)
The purpose of this principal's action research was to improve the pedagogical competence of teachers at SD Inpres XXXVII Uneng City in preparing assessment administration through academic supervision. The type of research used in this research is school action research. The activities in this study consisted of action planning, action implementation, observation, and reflection stages. Data collection techniques used class observation techniques. The observation instrument used was the teacher's ability assessment tool (APKG) in the form of a learning administration assessment instrument. The data analysis used is a comparative descriptive analysis technique. Quantitative data obtained is described in the form of words or explanations. Furthermore, data comparisons are carried out to ensure whether there is an increase in the ability of teachers in the assessment of learning administration. The results of the study show that academic supervision can improve the ability of teachers to prepare assessment administration in learning at SD Inpres XXXVII Uneng City 26.2%.